Master Pets Dog Hotel and Nursing Care - Gawkasem, Jate (2014)
The shift of attitude of dog owners towards dog humanization have resulted to constant increase spending of dog related products, while the increasing in dog population is only positive news for stakeholders involved in this industry as total spending would increase as well.